동북아농정연구포럼 2007 활동보고서 - 어명근 (한국농촌경제연구원, 2007)
The Forum for Agricultural Policy Research in Northeast Asia (FANEA) was established jointly by the Korea Rural Economic Institute (KREI), the Institute of Agricultural Economics and Development at the Chinese Academy of Agricultural Sciences (IAED/CAAS) and the Policy Research Institute under the Ministry of Agriculture, Forestry and Fisheries of Japan (PRIMAFF) in October 2003. This forum was launched to establish a collaborative relationship in agricultural research and related fields among Korea, China and Japan as part of their joint commitment to foster mutually beneficial research and development in the Northeast Asian countries. As a major activity of FANEA in 2007, the Korea Rural Economic Institute has participated in the 5th FANEA International Symposium in Beijing, China. The 5th FANEA International Symposium was held under the themes of “Rural Finance and Insurance, Aging and Rural Development in Northeast Asia, and Bio-Energy Development as well as its Impact on Northeast Agriculture. In this symposium, hosted by the Institute of Agricultural Economics and Development at CAAS, nine papers dealing with three themes were presented and discussed by participants from the three member countries. The Korea Rural Economic Institute also participated in the World Bank’s “End-of-Project Conference“ in Beijing. This conference was hosted by the IAED/CAAS for the discussion of the final report of the project on Chinese agricultural policy sponsored by the World Bank. The Korea Rural Economic Institute has established its China office in Beijing to initiate research on Chinese agriculture and agricultural policies. Researchers: Myong-Keun Eor(Ph.D), Chung-Gil Chung(Ph.D), Hyoung-Jin Jeon(Ph.D), Keun-Soo Han, Jing-Hu Li Report No: M84/Nov. 2007 E-mail address: myongeor@krei.re.kr